Congress in black and white race and representation in Washington and at home - Grose, Christian R. (Cambridge University Press, 2011)
"Race matters in Congress. This book argues that although electing black legislators yields meaningful outcomes in the lives of African-American voters in the United States, drawing affirmative action districts does not impact policy outcomes for black constituents"--